Factors influencing intention to become Agropereneur among youths / Sylvia Nabila Azwa Ambad ... [et al.] - Ambad, Sylvia Nabila Azwa; Sumin, Viduriati; Karia, Abdul Aziz; Abdul Hakim, Taufik; Albert Gisip, Imelda (Universiti Teknologi MARA, Perlis, 2021)
The objective of this research is to examine the relationship between Realistic, Investigative, Artistic, Social, Enterprising, and Conventional (RIASEC), and Shapero’s Entrepreneurial Event Theory (SEET) on the youth’s intention to be involved in agropreneurship. The data were collected by the self-reported in-person and electronic questionnaires from 269 youth in Sabah, Malaysia. The results revealed that realistic, investigative, enterprising and SEET plays a significant role in agropreneurship intention. Research on agropreneurship is still lacking, and to date, only a few studies have been published. The findings of this study enrich the existing literature, especially in Malaysia’s context. At the same time, this study assists the government and its agencies to identify and strengthen youth participation in the agriculture sector.